(untitled) (University Journal of Zoology, Rajshahi University, 2008)
The present investigation was carried out to detect the status of different productive and reproductive parameters of Black Bengal and Crossbred goats at Bandaikhara village under Atrai Upazilla of Naogaon district during the period of September to December/2005. The average age at first sign of heat of Black Bengal goats was better than that of Crossbred goats. In Black Bengal goat the average age at first kidding was 360.5±10 days, whereas, in crossbred goats it was 411.5±15.5 day. Significantly (P<0.01) lower the post partum heat period in Black Bengal goat than the crossbred goat. The average kidding interval in Black Bengal and Crossbred goats were 179±20 and 270±22 days respectively and differences are statistically significant (P<0.01). The usual numbers of kids at one time in Black Bengal goats vary from single to quadruplet. On the other hand, litter size of crossbred goat was single or twin. The average birth weight of Black Bengal goat was lower than Crossbred goats, which are statistically significant (P<0.05). The average body weight gain after 365 days is better in Crossbred than Black Bengal goats and statistically significant (P<0.01). The average milk yield in Crossbred goat was 1.05 liter/day, whereas, in Black Bengal goat, it produces milk that only nourished its kids. It was concluded that the reproductive performance like early maturity, larger litter size, shorter postpartum period, minimum kidding interval are better in Black Bengal goat. On the other hand productive performance like higher birth weight, maximum body weight gain, high milk yield, longer lactation length are suitable in crossbred goat. Key words: Black Bengal goat, Crossbred goat, Production, Reproduction, Performance Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 55-57